A simple and green analytical method for determination of glyphosate in commercial formulations and water by diffuse reflectance spectroscopy - da Silva, Aline Santana [UNESP]; Bedatty Fernandes, Flavio Cesar [UNESP]; Tognolli, Joao Olimpio [UNESP]; Pezza, Leonardo [UNESP]; Pezza, Helena Redigolo [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
This article describes a simple, inexpensive, and environmentally friendly method for the monitoring of glyphosate using diffuse reflectance spectroscopy. The proposed method is based on reflectance measurements of the colored compound produced from the spot test reaction between glyphosate and p-dimethylaminocinnamaldehyde (p-DAC) in acid medium, using a filter paper as solid support. Experimental designs were used to optimize the analytical conditions. All reflectance measurements were carried out at 495 nm. Under optimal conditions, the glyphosate calibration graphs obtained by plotting the optical density of the reflectance signal (A(R)) against the concentration were linear in the range 50-500 mu g mL(-1),with a correlation coefficient of 0.9987. The limit of detection (LOD) for glyphosate was 7.28 mu g mL(-1). The technique was successfully applied to the direct determination of glyphosate in commercial formulations, as well as in water samples (river water, pure water and mineral drinking water) after a previous clean-up or pre-concentration step. Recoveries were in the ranges 93.2-102.6% and 91.3-102.9% for the commercial formulations and water samples, respectively. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Glyphosate; Spot test; Diffuse reflectance spectroscopy; Commercial formulations; Water samples